2014
DOI: 10.1530/rep-13-0425
|View full text |Cite
|
Sign up to set email alerts
|

High-fertility phenotypes: two outbred mouse models exhibit substantially different molecular and physiological strategies warranting improved fertility

Abstract: Animal models are valuable tools in fertility research. Worldwide, there are more than 400 transgenic or knockout mouse models available showing a reproductive phenotype; almost all of them exhibit an infertile or at least subfertile phenotype. By contrast, animal models revealing an improved fertility phenotype are barely described. This article summarizes data on two outbred mouse models exhibiting a 'high-fertility' phenotype. These mouse lines were generated via selection over a time period of more than 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 27 publications
0
42
0
2
Order By: Relevance
“…Recent studies using different physiological and molecular strategies have recognized the existence of high-fertility male mice phenotypes that are probably attributable to the accumulation of endocrine (hormonal levels, e.g. testosterone), physiological (accelerated puberty) and behavioural advantages [46,47]. We therefore suggest that the fertility of AhR −/− male mice may depend on improved sperm functionality and on endocrine, physiological and/or behavioural advantages due to AhR depletion.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies using different physiological and molecular strategies have recognized the existence of high-fertility male mice phenotypes that are probably attributable to the accumulation of endocrine (hormonal levels, e.g. testosterone), physiological (accelerated puberty) and behavioural advantages [46,47]. We therefore suggest that the fertility of AhR −/− male mice may depend on improved sperm functionality and on endocrine, physiological and/or behavioural advantages due to AhR depletion.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study showed that C57BL/6-Ahr m1.2Arte null-mice (Taconic) have an accumulation of elongated spermatids and reduced fertility compared with wild-type mice in in vitro fertilization assays [36]. This difference could be explained by the fact that the in vivo assay used in our study may be a more physiological approach to determine differences in mice fertility because it is known that the mating itself and the different molecules (hormones and growth factors among others) that altogether constitute the sperm have a relevant impact in mice fertility [46,47]. In addition, the former study used C57BL/6JAhr b-1 as wild-type controls (Jackson Labs), and their different genetic background with respect to C57BL/6-Ahr m1.2Arte null-mice could have influenced the in vitro phenotypes found.…”
Section: Discussionmentioning
confidence: 99%
“…Here we focus on the FL1 mouse line, which, after more than 170 generations of breeding, has almost double the selection traits litter size, and litter birth weight in comparison to the control line (Ctrl). This is accompanied by no sign of growth retardation in the offspring litters and no alteration in pup survival after weaning (Langhammer et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…The advantage of this approach is its heterogeneity, which more closely mimics the phenotypical alterations in humans than single gene approaches like classical transgenic or knockout models. Breeding strategies and comparative data for these high-fertility mouse lines have been described previously (Dietl et al 2004, Langhammer et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Forkhead box O3 (FOXO3) in oocytes attenuates the postnatal decline of primordial follicles resulting in enhanced fertility (46). Using a different approach, outbred mice lines with high fertility have been obtained by selective breeding for more than 40 y (47).…”
mentioning
confidence: 99%